Multi-storey precast concrete framed structures - Elliott, Kim S.; Jolly, Colin K. (Wiley-Blackwell, 2013)
Precast reinforced and prestressed concrete frames provide a high strength, stable, durable and robust solution for any multi-storey structure, and are widely regarded as a high quality, economic and architecturally versatile technology for the construction of multi-storey buildings. The resulting buildings satisfy a wide range of commercial and industrial needs. Precast concrete buildings behave in a different way to those where the concrete is cast in-situ, with the components subject to different forces and movements. These factors are explored in detail in the second edition of
Keywords: Precast concrete construction; Tall buildings : Design and construction